Racial Disparities in Stroke Recurrence: A Population-Based Study. (29th November 2022) - Robinson, David Joseph; Stanton, Robert; Sucharew, Heidi; Alwell, Kathleen; Haverbusch, Mary; De Los Rios La Rosa, Felipe; Ferioli, Simona; Coleman, Elisheva; Jasne, Adam; Mackey, Jason; Star, Michael; Mistry, Eva A.; et al.
Abstract : Background and Objective: There are significant racial disparities in stroke in the United States, with Black individuals having a higher risk of incident stroke even when adjusted for traditional stroke risk factors. It is unknown whether Black individuals are also at a higher risk of recurrent stroke. Methods: Over an 18-month period spanning 2014–2015, we ascertained index stroke cases within the Greater Cincinnati/Northern Kentucky population of 1.3 million. We then followed up all patients for 3 years and determined the risk of recurrence. Multivariable survival analysis was performed to determine the effect of Black race on recurrence. Results: There were 3, 816 patients with index stroke/TIA events in our study period, and 476 patients had a recurrent event within 3 years. The Kaplan-Meier estimate of 3-year recurrence rate was 15.4%. Age-adjusted and sex-adjusted stroke recurrence rate was higher in Black individuals (HR 1.34, 95% CI 1.1–1.6; p = 0.003); however, when adjusted for traditional stroke risk factors including hypertension, diabetes, smoking status, age, and left ventricular hypertrophy, the association between Black race and recurrence was significantly attenuated and became nonsignificant (HR 1.1, 95% CI 0.9–1.36, p = 0.32). At younger ages, Black race was more strongly associated with recurrence, and this effect may not be fully attenuated by traditional stroke risk factors. Discussion: Recurrent stroke was more common among Black individuals, but the magnitude of the racial difference was substantially attenuated and became nonsignificant when adjusted for traditional stroke risk factors. Interventions targeting these risk factors could reduce disparities in stroke recurrence.